The clinical and prognostic role of changes in parameters of the hemostasis system and C-reactive protein in the development of thrombotic complications in oxygen-dependent patients with coronavirus disease (COVID-19) - V. V. Cherkaskyi; O. V. Riabokon (Patologìâ)
Aim. The purpose of our work was to find out the clinical and prognostic role of changes in hemostasis parameters and C-reactive protein (CRP) in the development of thrombotic complications in oxygen-dependent patients with coronavirus disease (COVID-19).